Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Keteladanan Dalam Membentuk Karakter Siswa Di Sdn 105 Baraka - Jamaluddin Hanapi; Jumsir Jumsir; Sudarmin Sudarmin; Muhammad Rizal; Amaluddin Amaluddin (Jurnal Sultra Elementary School, 2025)
Character education in elementary schools requires effective strategies to instill moral, spiritual, and social values ​​comprehensively in students. This study aims to analyze the implementation of Islamic Religious Education (PAI) learning based on teacher role models and its influence on student character formation at SDN 105 Baraka. The study used a qualitative approach with a case study method, involving PAI teachers in grades IV and V and a number of students selected purposively. Data collection techniques included classroom observation, semi-structured interviews, and documentation of learning activities. Data analysis was carried out through data reduction, presentation, and verification of conclusions with source triangulation to ensure the validity of the findings. The results showed that PAI teachers consistently displayed disciplined, honest, patient, and socially caring behaviors that served as real role models for students. This behavior encouraged students to imitate the teachers' positive attitudes, increasing cooperation, responsibility, social awareness, discipline, and honesty. In addition, teachers who exemplified religious practices and moral values ​​helped students internalize religious values ​​contextually, so that learning was not only theoretical but also practical. These findings demonstrate that teacher role-modeling-based learning is effective in shaping students' religious and social character and in creating a learning ecosystem that supports the sustainable development of Islamic character. This research provides implications for teachers and schools to continue strengthening daily role-modeling practices and personal interactions with students as key strategies for character development.